Response time, waiting time and service quality in emergency department - Nur Hidayat; Ahsan Ahsan; Masruroh Rahayu; Retno Lestari (Intelektual Pustaka Media Utama, 2020)
Response time and waiting time were key performance indicators in the emergency department of a hospital. This study will shed light on important factors contributing to service quality in emergency department of Indonesian public hospital by utilizing a cross-sectional design. About 117 patients were selected by simple random sampling techniques. Data observation sheets and a modified service quality instrument were used to measure health services in this department. Findings revealed that 83.8% patients felt satisfied with the services provided by emergency staff. Based on Kendall’s Tau test, waiting time had a significant relationship with service quality (p<0.05) compared to response time (p>0.05). The results of logistic regression test showed that waiting time had a higher value for Exp(B)= 3.522. In conclusion, waiting time was the most important factor affecting service quality in emergency department of Indonesian public hospital.